Mothers' experience of disrespect and abuse during maternity care in northern Ethiopia - Mengistu Welday Gebremichael; Alemayehu Worku; Araya Abrha Medhanyie; Yemane Berhane (Taylor & Francis Group, 2018)
Background: The provision of respectful and satisfactory maternity care is essential for promoting timely care-seeking behaviour, and ultimately ensuring the health and well-being of mothers and their babies. Disrespectful and abusive care has been recognized as one of the barriers to seeking timely maternity health services. However, the issue has not been adequately researched in community settings in low- and middle-income countries using validated measurement tools. Objective: This study was conducted to assess the extent of, and factors associated with, disrespectful and abusive maternity care reported by women who utilized facility-based delivery services in northern Ethiopia. Methods: We conducted a community-based cross-sectional study in Tigray, northern Ethiopia. Women who gave birth in the preceding year and visited health institutions for these deliveries were selected using a multistage cluster sampling procedure. Data were collected using a pretested questionnaire. Six domains of disrespect and abuse (D and A) were included in the questionnaire. Socio-demographic and obstetric related factors associated with D and A were tested using a negative binomial regression model. Results: Of the 1125 women in the sample, 248 (22%; 95% CI: 19.8%, 24.4%) reported at least one incident of D and A during delivery at a public health facility in northern Ethiopia. Higher incidents of D and A were reported by women who were older than 19 years at the time of delivery (aIRR = 2.649 (95% CI: 1.455, 4.825) compared to younger women. Incidents of D and A were reported more by women residing in urban areas, by women educated to the ninth grade and above, by women who experienced longer labour duration, and also by women who were not permitted to have support persons attend labour and delivery. Conclusions: A fifth of the women reported D and A while receiving care during labour and delivery. Policies and practices aimed at ensuring universal coverage for institutional deliveries need to promote respectful maternity care for women in all facilities.